2017
DOI: 10.1016/j.jvs.2016.10.077
|View full text |Cite
|
Sign up to set email alerts
|

Flow and wall shear stress characterization after endovascular aneurysm repair and endovascular aneurysm sealing in an infrarenal aneurysm model

Abstract: The different stent designs do not influence suprarenal flow. Lower WSS is observed in the caudal wall of the RA after EVAR and a higher shear rate after EVAS. All stented models have a small region of low WSS and high OSI near the distal outflow of the stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…In AA aneurysms, changes in flow patterns modulate inflammatory mechanisms in the vascular endothelium, causing aneurysm growth [4]. For AA aneurysms and stenotic lesions around the aortic bifurcation, in vitro data have shown that different treatment options generate different flow perturbations [5], [6], which can partly explain the different outcomes of these treatments. Post-treatment analysis of AA blood-flow patterns may make the follow-up schemes after endovascular treatment more patient-specific by predicting potential failure.…”
Section: Introductionmentioning
confidence: 99%
“…In AA aneurysms, changes in flow patterns modulate inflammatory mechanisms in the vascular endothelium, causing aneurysm growth [4]. For AA aneurysms and stenotic lesions around the aortic bifurcation, in vitro data have shown that different treatment options generate different flow perturbations [5], [6], which can partly explain the different outcomes of these treatments. Post-treatment analysis of AA blood-flow patterns may make the follow-up schemes after endovascular treatment more patient-specific by predicting potential failure.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of this novel pump compared with other commercially available pumps is its simplicity in generating the peripheral flow profiles. Traditionally, two needle valves located at renal artery outlets, an air chamber and a needle valve in series located at the combined common iliac artery outlets representing a twoelement Windkessel were used 1,2,17,18 to simulate the vessel resistance and peripheral compliance in order to generate flow profile with reverse flow in the early diastolic phase. With the reciprocating roller pump design, it can produce back flow in the peripheral artery without the use of renal artery flow in the circuit, therefore it simplifies the flow circuit for in vitro studies involving infrarenal aorta, iliac, femoral, and other peripheral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been successfully used by researchers to study and validate new treatment methods such as minimally invasive endovascular stent treatments. 1,2 In addition,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the oscillatory shear index is the mean fluctuation of wall shear stress vectors during the cardiac cycle, and a higher oscillatory shear index indicates that the wall shear stress vectors are substantially fluctuating. A high oscillatory shear index is also an important indicator of vascular remodeling, aneurysm progression, and rupture risk . Bürk et al reported a low wall shear stress and high oscillatory shear index in patients with a dilated thoracic aorta compared with healthy controls .…”
Section: Discussionmentioning
confidence: 99%